The impact of digital library resources usage on engineering research productivity: an empirical evidences from Pakistan. Issue 2 (3rd April 2017) - Khan, Amjid; Ahmed, Shamshad; Khan, Asad; Khan, Ghalib
Abstract : Purpose: The role of digital library resources (DLRs) in accelerating academic and research productivity has been acknowledged worldwide. The purpose of this study is to empirically explore the use of DLRs as a predictor of satisfaction and research productivity in the context of Pakistan to examine its impact on engineering research productivity. Design/methodology/approach: Given the research objectives, the most suitable methodology for this study is survey. The tool used for gathering the research data on the frequency of usage, purpose, satisfaction level and impact of DLRs usage on research productivity was questionnaires. Findings: The findings of this study showed that the frequency of use of DLRs and purposes of DLRs significantly contributed to the research students' satisfaction and research productivity. In addition, a significant relationship was found between the predictors (DLRs purposes, DLRs frequency) and outcome variables (users' satisfaction and research productivity). Thus, all five hypotheses are supported. The findings of this study further suggested the provision of information sources by university libraries to support research efforts and make a scientific knowledge-based society in the country. The findings are also significant for Higher Education Commission (HEC) authorities, university library administrators, Library and Information Science professionals/information providers to develop e-resources and formulate effective usage policies through which they could make effective use of DLRs. Originality/value: The rationale of the present study is to fill the gap by empirically investigating the association of users' satisfaction and research productivity with two dimensions of DLRs, namely, DLRs usage frequency and purposes of DLRs usage.